Characterization of Salmonella isolates obtained from pigs slaughtered at Wambizzi Abattoir in Kampala, Uganda - Tinega, G.M.; Magiri, E.; Kinyua, J.; Njahira, Moses N.; Erume, J.; Ejobi, F.; Tegule, S.; Mutua, Florence K. (2016)
Globally, non-typhoidal salmonellosis accounts for approximately 80.3 million cases of human infections annually. Estimates of salmonellosis due to consumption of pork or pork products is difficult to determine but, it ranges from < 1% to 25%. These invasive pathogens colonize intestinal mucosal surface but, they are self-limiting in health individuals due to a noble immunity. Utilization of antimicrobial agents in pig farming has been associated with the spread of resistant Salmonella species to man and the carrier status presents a major hazard to human health. This study examined 54 isolates for antimicrobial resistance, sequenced seven housekeeping genes, and performed Multi-Locus Sequence Type (MLST) analysis. We detected β-lactamase and tetA(B) genes in 100% and 80% of the isolates respectively. Data analysis using Codonbased Test of Neutrality analysis between sequences revealed P-value less than 0.05, an indication of strong forces of natural selection pressure acting at the sequence type level. Further data analysis using the Maximum Composite Likelihood Estimate of the Pattern of Nucleotide Substitution discovered frequencies of 0.177 (A), 0.244 (T/U), 0.263 (C), and 0.317 (G). The transition/transversion rate ratios were found to be k1 = 2.698 (purines) and k2 = 20.089 (pyrimidines) with an overall transition/transversion bias of R = 6.565, where R = [A*G*k1 + T*C*k2]/[(A+G)*(T+C)] further confirming that indeed the Salmonella isolates studied here were divergent. These results suggest that, Salmonella isolates of sequence types (STs) coexist in the intestine thereby providing for an efficient intestinal colonization and multiple adaptations. Our results offer general and rapid approaches for identifying genetic diversity of Salmonella serotypes in individual pig carcasses which can be adopted for molecular epidemiological surveys of important food contaminating bacterial pathogens.